Holiday Non-Price Rigidity and Cost of Adjustment - Georg Müller; Mark Bergen; Shantanu Dutta; Daniel Levy (Managerial and Decision Economics, 2007)
There has been increasing interest in understanding how firms undertake non-price adjustment activities, especially in situations where prices may be rigid despite changes in market conditions. Using scanner price data for over 4500 different food products from a large US supermarket chain, we document periods of rigidity in product additions and deletions: new products are less likely to be introduced, and existing products are less likely to be discontinued during holiday periods than throughout the rest of the year. We argue that this is due to higher costs of undertaking these kinds of product assortment activities during holiday periods. We discuss how this relates to the exiting literature on non-price adjustment and price rigidity.
Keywords: D21; L20; M21; M31; L81; 330; Non-price adjustment mechanism; cost of adjustment; price rigidity; holiday; product assortment; product introduction; product deletion; sticky price; rigid price; menu cost